(untitled) (Research, Society and Development, 2020)
Soybeans in natura can be used in the feed of confined animals as a source of protein and energy. We measured consumption, performance, in vivo biometry, and metabolic profiles lambs fed whole grain soybean in natura. We used Ile de France breed lambs, weaned and confined in a completely randomized design with six repetitions and three treatments: Control, soybean grain (SG) 6.25%, and SG 14% (based on dry matter) in feed. The control and SG 6.25% groups showed higher average daily gain (0.296 kg/day) and total weight gain (17.57 kg) than did the SG 14% group. There were no differences among groups in terms of consumption of dry matter, protein, neutral detergent fiber, acidic detergent fiber, or feed conversion. The inclusion of soybean grain was associated with linear increases in consumption of ethereal extract, and in percentage of live weight. There were no differences among groups in terms of concentrations of studied metabolites. Regarding in vivo biometrics, the control treatment and SG 6.25% groups were superior in terms of conformation and body conditions. Inclusion of soybean whole grain in natura in the feed of confined lambs may be reduced consumption of dry matter and average daily weight gain.